Comparative study of UV spectroscopy, RP-HPLC and HPTLC methods for quantification of antiviral drug lamivudine in tablet formulation - Komal Somkuwar; Prafulla Sabale; Vaibhav Sawale; Priya Rahangdale (SpringerOpen, 2024)
Abstract Background In the current study, estimation of lamivudine (LMU) by UV spectroscopy, reverse-phase HPLC (RP-HPLC) and HPTLC methods in tablet formulation was developed, and comparative studies between the methods were investigated by analytical results and statistical test analysis of variance (ANOVA) to find out best method. In the UV spectral method, LMU was quantified at 271 nm absorption maxima using methanol as the solvent. In the RP-HPLC method, the Shimadzu C18 column (250 mm × 4.6 mm i.d., 5 µm particle size) was employed for chromatographic separation. The mobile phase used consists of methanol: water (70:30 v/v) in an isocratic mode with a 1.0 mL/min flow rate. In the HPTLC method, the chromatogram was developed on a pre-coated plate of silica gel 60 F254 with a mobile phase composition of chloroform: methanol (8:2 v/v). The quantification was performed at an absorbance mode of 271 nm by densitometry. The methods were validated according to the International Conference on Harmonization (ICH) guideline Q2 (R1). The degradation conditions were employed as per ICH guidelines Q1A(R2) and Q1B which include acid, alkaline, neutral, thermal and photostability to determine the intrinsic stability of the drug in varied environmental conditions. Results LMU absorption maxima was found to be 271 nm. The retention time of LMU was 3.125 min, and the total analysis time was 5 min. The Rf value of LMU was 0.49-0.62. The methods were linear within 2-12 μg/mL range. The correlation coefficient (r2) for UV, HPLC and HPTLC was 0.9980, 0.9993 and 0.9988, and percent recoveries were calculated as 98.40-100.52%, 99.27-101.18% and 98.01-100.30%, respectively, with percentage relative standard deviation (RSD) less than 2% showing that methods were precise and accurate. Conclusion Developed UV, RP-HPLC and HPTLC methods are free from intervention caused by excipients present in tablets and thus can be used for regular quantitative analysis of LMU in tablet formulation. Based on analytical results and statistical tests, ANOVA, it is inferred that the HPLC method is best for LMU quantification tablet formulation due to its high reproducibility, good retention time and sensitivity; it has a higher percent recovery and has less analysis time, i.e., 5 min. The degradation peaks were well separated from the LMU peak indicating stability of the HPLC method.